Characteristics and outcome of nosocomial bloodstream infection in patients with acute-on-chronic liver failure. Issue 1 (January 2021) - Su, Haibin; Tong, Jingjing; Liu, Xiaoyan; Li, Chen; Chen, Jing; Xu, Xiang; Guan, Chongdan; Peng, Yuhui; Yan, Lilong; Ning, Peng; Li, Hui; Zhang, Lina; et al.
Abstract : Aim: Patients with acute-on-chronic liver failure (ACLF) have a high risk of developing infections while hospitalized . Nosocomial bloodstream infection (BSI) is not uncommon, particular in patients who receive invasive operation, which may have negative impact on prognosis. In this study, we aim to investigate the characteristics and short-term outcome of nosocomial BSI in patients with ACLF. Methods: Sixty-three patients with ACLF and nosocomial BSI from January 2014 to December 2015 were retrospectively studied. Clinical characteristics and distribution of bacteria at the time of BSI onset and short-term mortality were collected. Results: The most common etiology of ACLF was hepatitis B virus infection. Eighty-one percent of ACLF patients had other types of infections at BSI onset. Gram-negative bacteria (77.8%) were the main pathogens, among which Escherichia coli was responsible for 46.9%. Staphylococcus epidermidis was the main Gram-positive bacteria. The most prevalent multidrug resistance (MDR) bacteria was extended-spectrum β-lactamase (ESBL)-producing E. coli. The overall 28-day mortality rate was 42.9%. Multivariate analysis found that model for end-stage liver disease (MELD) score and number of organ failures were predictors of 28-day mortality. The area under the receiver operating characteristic of the numbers of organ failures to predict 28-day mortality was higher than MELD score (0.833 vs. 0.784, 0.4099), but without significant difference. Conclusion: Gram-negative bacteria were the most prevalent pathogens and ESBL-producing bacteria were responsible for most of the MDR bacteria in patients with ACLF and nosocomial BSI. Higher MELD score and multiorgan failure were associated with worse outcomes.